Residual stresses due to foreign object damage in laser-shock peened aerofoils: Simulation and measurement. (March 2015) - Lin, B.; Zabeen, S.; Tong, J.; Preuss, M.; Withers, P.J.
Highlights: Residual stresses due to ballistic impacts in laser shock peened aerofoil specimens were simulated using 3D FE analysis. Johnson – Cook material and dynamic failure models were employed in the simulations. The numerical results compared favourably with the experimental measurements by synchrotron X-ray diffraction. Abstract: Foreign object damage (FOD) to the leading edge of aerofoils has been identified as one of the main life-limiting factors for aeroengine compressor blades. Laser-shock peening (LSP) has been proposed as a means of increasing the material's resistance to such impact damage. In this work, a three-dimensional finite element (FE) model has been developed to simulate the residual stresses due to head on (0°) and 45° impacts by a cuboidal projectile on aerofoil specimens treated with LSP. The Johnson – Cook (JC) material model was employed to describe the strain rate-dependent material behaviour; whilst the Johnson – Cook dynamic failure model was considered in 45° FOD simulation, where significant loss of material occurred. The strain rate sensitivity of the model at selected high strain rates was assessed against the data from the literature. The numerical results from the simulation of head-on impact were compared with the measurements by depth-resolved synchrotron X-ray diffraction on the mid-plane. The models were then used to predict the 3D residual stress distributions due to 0° and 45° FOD impacts, and the results were compared with the strain maps obtained from high-energy synchrotron X-ray diffraction. Good to excellent correlations between the simulations and the measurements have been found.